Nanostructured Conductive Polymers 2010
DOI: 10.1002/9780470661338.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline Nanostructures

Abstract: Polyaniline (PANI) is one of the most extensively studied conducting polymers because of its simple synthesis [1] and doping/dedoping chemistry [2], low cost, high conductivity, and excellent environmental stability. PANI has a wide applicability in rechargeable batteries [3], erasable optical information storage [4], shielding of electromagnetic interference [5], microwave-and radar-absorbing materials [6], sensors [7], indicators [8], catalysts [9], electronic and bioelectronic components [10], membranes [11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 520 publications
(618 reference statements)
0
7
0
Order By: Relevance
“…For instance, the SA of PANI nanofibers obtained with different dopant acids in conventional synthesis were reported to be in the range of ∼35–55 m 2 g –1 , while the conventionally synthesized PANI had a SA of 15 m 2 g –1 . Because microwave-enhanced synthesized PANI samples have larger specific SA, this material may act as a promising catalyst support or chemical sensor carrier . It has been reported that a classical microwave was used for preparation of hypercrosslinked PANI with permanent porous structure and SA which exceed 630 m 2 g –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the SA of PANI nanofibers obtained with different dopant acids in conventional synthesis were reported to be in the range of ∼35–55 m 2 g –1 , while the conventionally synthesized PANI had a SA of 15 m 2 g –1 . Because microwave-enhanced synthesized PANI samples have larger specific SA, this material may act as a promising catalyst support or chemical sensor carrier . It has been reported that a classical microwave was used for preparation of hypercrosslinked PANI with permanent porous structure and SA which exceed 630 m 2 g –1 .…”
Section: Resultsmentioning
confidence: 99%
“…PANI is typically produced through the oxidative polymerization of aniline, using a strong oxidizing agent such as ammonium persulfate (APS) or potassium iodate (KIO 3 ) in a strong acidic solution such as 1 M HCl. , Synthesized in this way, PANI possesses a granular morphology and is characterized by high conductivity. However, under certain conditions PANI can form nanostructuresnanotubes, nanorods, nanofibers, and nanospheresthe formation and structural characteristics of which have been extensively studied and reported. As the field of nanodevices becomes more commercially attractive, the widespread adoption of nanomaterials is limited by a need for the development of a methodology that can provide large-scale quality products. Over the past few years, considerable interest has emerged in the use of microwave irradiation in inorganic and organic synthesis. , In many of the published examples, microwave heating has been shown to dramatically reduce reaction times, increase product yields, and enhance product purities by reducing unwanted side reactions compared to conventional heating methods…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, conducting polymers have attracted great interest due to their potential use as inexpensive and flexible organic (semi)conducting layers in various applications such as electronics, photovoltaic devices, and supercapacitors . In recent years, studies toward the formation of one-dimensional (1-D) nanostructures such as fibers, wires, rods, and tubes of conducting polymers have flourished because of the proven advantages of such materials in many applications that lead to superior performance characteristics compared to those of their currently used bulk counterparts. Among all the conducting polymers, polyaniline (PANI) nanofibers are one of the most intensively studied systems because of their remarkable propensity to form anisotropic structures and also the unique, simple acid−base doping−dedoping chemistry . Synthetic routes toward PANI nanofibers include template-guided methods such as those using zeolites, , surfactants or bulky dopant acids, nanowire seeding, and biotemplates .…”
Section: Introductionmentioning
confidence: 99%
“…Although the compound itself was discovered over 150 years ago [37], only since the early 1980s it has truly captured the attention of the scientific community due to its significant electrical conductivity. Amongst the family of conducting polymers and organic semiconductors, polyaniline has many appealing processing properties, being one of the most studied conducting polymers of the past 50 years: in bulk, as thin films, or as nanostructures [13,19,[38][39][40][41][42][43][44][45][46]. PAni exhibits significant absorbance in the microwave range, and it is also frequently used in gas sensors because of its capability to convert chemical interactions into electrical signals [13,19,39].…”
Section: Methodsmentioning
confidence: 99%